Manfred Görlach. English Words Abroad - Abecassis, Michaël (Lexikos, 2004)
Since the Second World War, the infiltration of English into the Romance languages has remarkably increased, notably diffused by various media such as newspapers, radio and television broadcasts, popular music, and the internet. This comprehensive, thorough and authoritative work, whose data has been collected from these different sources, strives to quantify the spread of Anglicisms within individual foreign languages.